The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/1413-70542018423022317
|View full text |Cite
|
Sign up to set email alerts
|

Variability and genetic diversity study in an advanced segregating population of rice with bacterial blight resistance genes introgressed

Abstract: Bacterial blight disease of rice caused by Xanthomonas oryzae pv. oryzae is one of the most important widespread disease around the globe and can cause severe yield reductions of up to 30% of the total yield. Genetic variability was studied in 54 families of CB 174 R × IRBB 60 rice with bacterial blight resistance genes introgressed at the Department of Rice, Tamil Nadu Agricultural University, Coimbatore, India. Traits such as plant height and the number of productive tillers per plant were found to have nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…Heritability estimates for different traits ranged from 21 per cent to 84.2 per cent, while as genetic advance as per cent of mean ranged from 5.31 per cent to 39.52 per cent. Govintharaj et al, [10]; Adhikhari et al, [11] and Dhavaleshvar et al, [12] also found similar results in their research findings. Traits viz., total number of tillers per plant, number of effective (productive) tillers per plant, grain yield per plant and grain yield per plot were found to have high genetic advance (GAM) coupled with high heritability implying that these traits have been efficiently inherited from generation to generation.…”
Section: Resultssupporting
confidence: 65%
“…Heritability estimates for different traits ranged from 21 per cent to 84.2 per cent, while as genetic advance as per cent of mean ranged from 5.31 per cent to 39.52 per cent. Govintharaj et al, [10]; Adhikhari et al, [11] and Dhavaleshvar et al, [12] also found similar results in their research findings. Traits viz., total number of tillers per plant, number of effective (productive) tillers per plant, grain yield per plant and grain yield per plot were found to have high genetic advance (GAM) coupled with high heritability implying that these traits have been efficiently inherited from generation to generation.…”
Section: Resultssupporting
confidence: 65%
“…In accord with our findings, grain yield was reported for a higher phenotypic and genotypic coefficient of variation by several researchers. These researchers also find phenotypic components higher over genotypic components of variation in the studied traits (Abebe, Alamerew, & Tulu, 2017;Adhikari, Joshi, Shrestha, & Bhatta, 2018;Govintharaj, Manonmani, & Robin, 2018;Kishore, Srinivas, Nagabhushanam, Pallavi, & Sameera, 2015;Tiwari, Tripathi, Tripathi, Khatri, & Bastola, 2019). Broad sense heritability values were recorded highest for DTF (97.40%), DTM (91.78%), PHT (86.62%), HI (87.17%), and TGW (71.06%) whereas found moderate for PL (63.22%), BY (47.45%), and GY (64.26%) respectively.…”
Section: Genetic Parametersmentioning
confidence: 70%
“…The study of distribution using skewness and kurtosis provides information about the nature of gene action and the number of genes controlling the traits (Govintharaj et al 2018). Positive skewness is associated with complementary gene action, while negative skewness is associated with duplicate (additive × additive) gene interactions.…”
Section: Resultsmentioning
confidence: 99%